A Systematic Review of Reminiscence Therapy for Older Adults in Taiwan. Issue 2 (April 2018) - Yen, Hsin-Yen; Lin, Li-Jung
ABSTRACT: Background: Population aging is an increasing phenomenon in many countries around the world. It has been estimated that more than one quarter of all older adults experience a mental or neurological disorder or disease such as dementia, depression, anxiety, and substance abuse. Reminiscence is a popular treatment for enhancing well-being in older adults. Previous studies have shown that reminiscence therapy improves the cognitive functions, behaviors, and other psychosocial outcomes in older adult patients. The themes and materials that are used in reminiscence treatments for the older adults in Taiwan differ from those used in other countries because of Taiwan's unique historical background and culture. Purpose: The main purpose of the current study was to review systematically the application and outcomes of reminiscence therapy in Taiwan. Method: The terms "reminiscence, " "dementia, " "Alzheimer's disease, " and "Taiwan" were used in an Integrated Resources Search that was conducted at National Taiwan Normal University. Sixteen articles were systematically reviewed using a synthesis of two matrices of experimental designs and intervention designs. Result: Reminiscence group sizes ranged between 7 and 12 participants, session frequencies were all once a week for periods lasting between 4 and 16 weeks, and session durations ranged from 30 minutes to 2 hours. The memories of the participants were stimulated using materials dating from their youth such as Taiwanese folk songs, toys, photos, radio programs, newspapers, and food and drinks. In terms of research methodology, most of the studies that were reviewed used quasi-experimental designs without random assignment or control group due to sample size. A minority of the reviewed studies applied the randomized controlled treatment method. Only a few of the studies evaluated indicators in pretest, posttest, and follow-up periods. The results of these studies identified several benefits of reminiscence therapy in Taiwanese older adults, including improvements in cognitive function, anxiety, depressive symptoms, self-esteem, life satisfaction, and personal interaction. Conclusions: Reminiscence is a good noninvasive treatment for the prevention and treatment of mental diseases in Taiwanese older adults. Furthermore, reminiscence promotes mental health in older adults. Finally, this study provides recommendations for further study and clinical application of reminiscence therapy in Taiwan.